Improving Students’ Vocabulary Mastery through TPR Storytelling - Nuraeningsih Nuraeningsih; Rusiana Rusiana (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
Teaching English for primary school students highly emphasizes on vocabulary. It is understandable since they are at the first stage of learning the language. Unfortunately, in many teaching practices, vocabulary is taught in an isolated way without the presence of meaningful context. Vocabularies are often given in the form of long list to be memorized. Actually, the aim of learning vocabulary is to equip the students to be ready to use the language (i.e. speaking). Therefore, here, Total Physical Response Storytelling (TPRS) is to meet with the students’ need. TPR Storytelling is one of foreign language teaching methods proposed by Blaine Ray of Bakersfield, California. Using TPR Storytelling (TPRS), teachers told two stories, Crocodile Tears and The Very Hungry Caterpillar and students acted those stories out. The research was conducted to know the influence of TPR Storytelling on the student’s vocabulary mastery. It elaborates what works and what does not work in implementing Total Physical Response Storytelling to teach vocabulary. To achieve the purpose of this research, a Classroom Action Research consisting of two cycles was conducted. The subjects of the research were Second Graders of SD in Kudus, Centra Java, Indonesia, with the number of 20 students. Three instruments were used to collect the data, i.e.: test, observation, & questionnaire. The result of the research shows that the use of TPRS can improve the students’ vocabulary mastery. The students’ responses on the use of TPRS are also positive. Therefore, teachers are expected to make use of other stories by considering vocabularies that meet with the syllabus and the students’ need with the support from the institution.